Soil erodibility assessment in a pasture and forest remnant using the Indrbitzen device - Ribeiro, Admilson Irio [UNESP]; Gonzáles, Luis Fernando; Longo, Regina Márcia; Medeiros, Gerson Araújo de [UNESP]; Rosa, André Henrique [UNESP]; Lourenço, Roberto Wagner [UNESP]; Fengler, Felipe Hashimoto (My University, 2013)
Brazil has the largest cattle herd in the world with approximately 200 million head. An important feature of the Brazilian cattle industry is that most of its herd is raised on pasture, which constitutes one of the most economical and practical ways to produce and provide food for cattle. However, this production model is mishandled and can lead to soil degradation. Maintaining soil quality is essential for the conservation of natural ecosystems and the areas of production, thus soil quality improves the conditions for biogeochemical cycles. In this context, the objective of this study was to develop a device for testing the Inderbitzen way of assessing soil erodibility in two situations of usage and occupation. Therefore, one area was used as a sample collection occupied by grazing and the other as a forest fragment; both located in the city of Sorocaba in Sao Paulo State, Brazil. Thus, we concluded that the proposed device – the Inderbitzen – proved capable of assessing soil erodibility of the pasture and remnant forest. Accordingly, there was a tendency for a smaller loss of forest soils in the remnant when compared to the degraded pasture. The greatest resistance of the soil erosion in the forest remnant may be associated with the amount of organic matter released by the forest litter in all its diversity, influencing the quality of the structure of aggregates. Keywords: erosion, forest remnant, degraded pasture, Inderbitzen test.
Keywords: erosion; forest remnant; degraded pasture; Inderbitzen test